2017
DOI: 10.3892/ol.2017.6080
|View full text |Cite
|
Sign up to set email alerts
|

Effects of programmed death-ligand 1 expression on OK-432 immunotherapy following transurethral resection in non-muscle invasive bladder cancer

Abstract: The present study aimed to investigate the effect of the negative costimulatory molecule programmed death-ligand 1 (PD-L1) on immunotherapy with OK-432, following transurethral resection of bladder tumors in non-muscle invasive bladder cancer (NMIBC), and to elucidate the underlying mechanism. PD-L1 was detected by immunohistochemical staining in tumor specimens from 55 cases of NMIBC following postoperative immunotherapy with OK-432. The PD-L1 mRNA and protein expression levels were measured in the bladder ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 38 publications
0
8
0
Order By: Relevance
“…Programmed death-ligand 1 (PD-L1), also known as surface antigen differentiation cluster 274 (CD274) or B7 homolog (B7-H1), is a type 1 transmembrane protein encoded by the CD274 gene. Upregulation of PD-L1 expression can enable cancer cells to escape host immune recognition, thereby increasing the risk of tumor invasion and metastasis (Francisco et al, 2010;Goltz et al, 2016;Liu et al, 2017;Yaghoubi et al, 2019;Zhou et al, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…Programmed death-ligand 1 (PD-L1), also known as surface antigen differentiation cluster 274 (CD274) or B7 homolog (B7-H1), is a type 1 transmembrane protein encoded by the CD274 gene. Upregulation of PD-L1 expression can enable cancer cells to escape host immune recognition, thereby increasing the risk of tumor invasion and metastasis (Francisco et al, 2010;Goltz et al, 2016;Liu et al, 2017;Yaghoubi et al, 2019;Zhou et al, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…The characteristics of the included studies are shown in Table 1. The 27 studies included 4,032 patients; 716,18,20,21,23,24,26studies originated from Asian countries/regions (Japan, Taiwan, China), 925,27,29-35studies were multicentre and global studies, and the remaining studies originated from the United States, Germany, and France. The sample size ranged from 37 to 423.…”
Section: Resultsmentioning
confidence: 99%
“…Programmed death-ligand 1 (PD-L1) is a member of the B7 family of costimulatory molecules; it is a cell surface glycoprotein that promotes apoptosis by binding to its surface receptor, programmed cell death-1 (PD-1), in T cells and B cells, thereby inhibiting host immune function. PD-L1 has also been implicated in tumor immune escape [3,4,5].…”
Section: Introductionmentioning
confidence: 99%